Collaborative tools: computer science students' skills versus software industry needs. Issue 3 (11th March 2015) - Medina‐Dominguez, Fuensanta; Sanchez‐Segura, Maria‐Isabel; Moreno, Ana; Santin, Daniel
Abstract: Software companies encourage and further the use of collaborative tools and skills at the work place in pursuit of the benefits of their use: they improve communication, productivity and efficiency, and competitiveness. Besides, undergraduate and graduate software engineering computing curricula recommend subjects related to effective cooperative working and group learning. In order to align industry needs and curricula recommendations, universities should provide graduates with the collaborative knowledge and skills that will be required when they finish their degrees and join the labor market. In this scenario, we asked three questions: Are collaborative tools beneficial to software projects? Is it easier for graduates with knowledge and skills of collaborative tools to find a job? Do enterprises use collaborative tools as a marketing strategy for the recruitment process or are they really empowering their employees to use collaborative tools? We devised a survey which was administered to 86 recent computer science graduates. We applied statistical techniques to analyze the responses. We conclude that graduates skilled in the use of collaborative tools do find it easier to get jobs, and companies are not only looking for people with collaborative skills but also regularly use collaborative tools in their work processes. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Students should be trained in collaborative tools skills that are clearly demanded by industry during their undergraduate studies. New methodological and technological trends should be dynamically incorporated into the curriculum in the slots set aside for elective subjects in the senior years of degree courses. Students will be trained in not only the general but also the specific skills demanded by the labor market, which the students will be joining after completing their studies.